Pengaruh Online Learning Terhadap Minat, Motivasi Dan Prestasi Belajar Mata Pelajaran Agama Buddha pada Peserta Didik SMP Maitreyawira Palembang: STAB Maitreyawira - Jordy Steffanus; Sonika Sonika; Hosan Hosan (STAB Maitreyawira, 2022)
The purpose of this study was to determine the relationship simultaneously and partially between online learning on interest, motivation and learning achievement of students in Buddhist subjects at SMP Maitreyawira Palembang. This study used a quantitative method. The samples taken in the study were 48 people using purposive sampling technique. This study used a questionnaire which was distributed to 48 students. The analysis technique used was multiple linear regression analysis. The results of the analysis of research data showed that the regression value of 0.914 indicated that there was a significant relationship between online learning and interest, motivation and learning achievement. Fvaluecalculated (74.543) was greater than Ftable(2.82), this meansthat there was a joint significant influence between online learning on interest, motivation and learning achievement. The value of the coefficient of determination showed that the percentage of the influence of online learning on interest, motivation andlearning achievement is 83.6% while the remaining 16.4% was influenced by other variables. And obtained the value of the ttest, the tvalueof (3.963), motivation was (3.022), and learning achievement was (2.893) with a ttableof (1.679). This shows that online learning partially has a significant relationship to students' interest, motivation and learning achievement.